The teaching of literature in a Singapore secondary school: disciplinarity, curriculum coverage and the opportunity costs involved. Issue 3 (3rd July 2017) - Towndrow, Phillip; Kwek, Dennis Beng Kiat
Abstract: Set against the backdrop of reinvigorating the study of literature and concerns about the adequate preparation of students for the world of work, this paper explores how a Singapore teacher presented a literary text in the classroom. Drawing on data from a large-scale representative sample of Singapore schools in instruction and assessment practices, we discuss some of the potential consequences of instructional choice-making from a disciplinary perspective. Our findings suggest, for example, that when teacher-dominated discourse and interpretations dominate, instructional flexibility and responsiveness are correspondingly limited and restricted. These courses of action, we contend, may occur contrary to teachers' plans and expectations. The paper closes by making a call for further longitudinal research across multiple research sites into the nature of literature pedagogy that has a strong disciplinary focus.